Online Coordination Scheduling for Distributed Satellite System with Limited Communication - Li, Guoliang (2019 4th International Conference on Communication and Information Systems (ICCIS), 2019)
This paper focuses on online management of Distributed Satellite System under dynamic environment. In reality, the inter-satellite communication is limited by practical reasons. The objective is to maximize the total profit of whole system subject to communication time window constraints and observation time window constraints. Firstly, Contract Net Protocol (CNP)-based mechanism is presented to solve this problem. Then, we propose two novel online coordination mechanisms based on Synchronous and Asynchronous communication respectively. The two proposed online coordination mechanisms are compared with CNP-based mechanism. Computational experiments indicate that when the communication resources are scarce, Synchronous Communication-based mechanism is the best choice for the balance between the profit and the communication cost. When the communication resources are relatively sufficient, Asynchronous Communication-based mechanism is preferred for the good performance on profit and percentage of scheduled urgent tasks.